Conceptualizing music : cognitive structure, theory, and analysis. - Zbikowski, Lawrence Michael (AMS studies in music, 2002)
Music theory is often seen as an arcane and somewhat forbidding discipline which stands at a distance from the sweet pleasure and sensuous thrill that is music.Theory, according to this view, is concerned with scales and chords and intervals, or with complicated and highly abstract systems of musical relationships. It is not concerned with how music captivates us. But Lawrence Zbikowski argues that this common view of music theory is wrong. Theorizing about music is something we do every time we try to make sense of our musical experience, and involves the same cognitive capacities we use to make sense of the world as a whole. The play of concepts and conceptual structures typical of music theory is thus not something remote from our appreciation of music, but is instead basic to it. Zbikowski draws on recent research in cognitive psychology, cognitive linguistics, and artificial intelligence research to show how we employ basic cognitive capacities for the understanding of music. The theories of music that result range from the informal to the highly complex, but all make use of the same cognitive processes to give an account of musical structure. In the first part of the book Zbikowski provides an overview of recent research in cognitive science, and shows the roles categorization, cross-domain mapping, and conceptual models play in musical understanding. Each discussion is framed around specific musical topics, such as motivic transformation, text painting, and the ways in which we structure our understanding of a specific musical domain. In the second part of the book he presents analytical studies of specific musical issues, illustrated with discussions of a diverse repertoire that ranges from string quartets by Mozart and Beethoven, to songs by Schubert and Brahms, to George Gershwin’s "I Got Rhythm." Through these analyses he engages such topics as the relationship between processes of categorization and musical syntax, the problem of musical ontology, text-music relations, and conceptions of musical form and musical hierarchy -- Présentation de l'éditeur.